THE EFFECT OF DIFFERENT SUBSTITUTION MEALS TO PHYSICAL AND CHEMICAL QUALITY OF INSTANT NOODLES - Tri Winarni Agustini; Sri Haryati (JOURNAL OF COASTAL DEVELOPMENT, 2007)
Fishery resources including scadjish (Restrelliger sp.), Small Shrimp (A cetes sp.), and Swimming crab (Portunus pelagicus) have a high nutritional value. It can be processed into meal through several procedures, so the product can be used as a substituted material to create a nutritious instant noodle. The objectives of this research were to study the #ct of jish meals as substituted material with diferent concentration to the physical and chemical quality of instant noodle produced and to find out what the optimal composition also whether there are any interaction of both factors. This research used factorial experimental design based on group random design, consisted of 2 factors: factor A (different fish meals): Scad fish meal (A I), Small shrimp meal (A2) and Swimming crab (Portunus pelagicus) meal (A3); and factor B (d@rent concentration) consisted of 5 level: 0%, 5%, I 0%, 15% and 20%. The analysis used was anabtsis of variance (ANOVA) followed by HSD 5%. The results of this research showed that there was signyicant eyct (P<0, 05) of dmrent fshmeals and concentration to the physical and chemical quality of the product. The type of meal has a signyicant @0t (P<0, 05) to the tensile strength. moisture, ash, protein, fat, and calcium content. Concentration treatment has a signficant eject (P<0,005) to the physical (brightness) and chemical quality, but there was no interaction of treatment to tensile strength, brightness, fat, and co/or of instant noodles (P>0, 005). The optimal compositions of protein rate (I 9, 77%) were achieved by 20% seadfishmeal; fat rate (19,93%) by 20% Small Shrimp meal, and calcium rote (42,525%) by 20% swimming crab meal. The favorite composition for instant noodle was achieved by I 0% swimming crab meal